2003
DOI: 10.1007/s00425-003-1068-6
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced fluorescence changes in Phycomyces : evidence for blue light-receptor associated flavo-semiquinones

Abstract: Light-induced fluorescence changes (LIFCs) were detected in sporangiophores of the blue-light-sensitive fungus Phycomyces blakesleeanus (Burgeff). The LIFCs can be utilized as a spectrophotometric assay for blue-light photoreceptors and for the in vivo characterization of their photochemical primary reactions. Blue-light irradiation of sporangiophores elicited a transient decrease and subsequent regeneration of flavin-like fluorescence emission at 525 nm. The signals recovered in darkness in about 120 min. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…also as red light sensors, since the absorption of the neutral radical state of flavoproteins, in most cases, extends well beyond 600 nm (Müller et al, 1972). Previous studies suggested a role of the neutral radical in photoreceptors, but only as the signaling state, which is formed from the oxidized state by the absorption of blue light (Galland and Tölle, 2003). Accordingly, illumination of the radical would then lead to depletion of the signaling state.…”
Section: Identification Of a Flavoprotein Mediating A Red Light Responsementioning
confidence: 99%
“…also as red light sensors, since the absorption of the neutral radical state of flavoproteins, in most cases, extends well beyond 600 nm (Müller et al, 1972). Previous studies suggested a role of the neutral radical in photoreceptors, but only as the signaling state, which is formed from the oxidized state by the absorption of blue light (Galland and Tölle, 2003). Accordingly, illumination of the radical would then lead to depletion of the signaling state.…”
Section: Identification Of a Flavoprotein Mediating A Red Light Responsementioning
confidence: 99%
“…The data presented in this work can be best explained by the assumption that gravistimulation modulates the pool of these flavo-semiquinones that need to be present in darkness and that are substantially boosted by blue-light irradiation. Evidence for the presence of such flavo-semiquinones in darkness and particularly after blue-light irradiation has been presented recently for P. blakesleeanus (Galland and Tö lle, 2003). We thus propose that graviperception involves and largely depends on the blue-light photoreceptor system.…”
Section: Synergism Between Photo-and Graviperception: a Model For Thementioning
confidence: 62%
“…According to Galland and Tölle (2003), natural fluorescence (as seen in living tissue cultures) is due in large part to substances such as flavins and porphyrins, e.g. chlorophyll.…”
Section: Resultsmentioning
confidence: 99%